Save me a seat - Weeks, Sarah; Varadarajan, Gita (Scholastic Press, 2016)
Ravi has just moved to the United States from India and has always been at the top of his class; Joe has lived in the same town his whole life and has learning problems--but when their lives intersect in the first week of fifth grade they are brought together by a common enemy (the biggest bully in their class) and the need to take control of their lives.